Low-keV Virtual Monoenergetic Imaging for Bronchial Artery Visualization on Photon-Counting Detector Computed Tomography - Xuyang Sun; Tetsu Niwa; Takakiyo Nomura; Ryoichi Yoshida; Kazuo Koyanagi; Jun Hashimoto (Diagnostics)
Background/Objectives: This study aims to determine the optimal use of virtual monoenergetic imaging (VMI) for visualizing the bronchial artery on photon-counting detector computed tomography (PCD-CT). Methods: We evaluated the visibility of the bronchial artery on PCD-CT in 34 consecutive patients with esophageal cancer (twenty-eight men, six women; mean age, 70.2 years) prior to surgery. Region-of-interest measurements were taken at the right bronchial artery at the tracheal bifurcation level, mediastinal fat, and the erector spinae muscles on contrast-enhanced early-phase CT. We compared the CT attenuation of the bronchial artery, image noise, and contrast-to-noise ratio (CNR) across VMI at 40, 50, 60, and 70 keV. Additionally, two radiologists performed a subjective image quality assessment by comparing VMI at 40, 50, and 60 keV with 70 keV, rating bronchial artery enhancement, border clarity, peripheral visibility, and image noise. Results: CT attenuation, image noise, and CNR significantly differed across VMI energy levels (p < 0.00001). Lower-keV VMI demonstrated higher CT attenuation and increased noise but also higher CNR (all p < 0.05). Both radiologists rated bronchial artery enhancement, border clarity, and peripheral visibility higher at 40 and 50 keV than at 70 keV, with the highest scores observed at 40 keV (all p < 0.05). Observer 1 noted slightly increased noise at 40 and 50 keV, while observer 2 observed this effect at 40 keV compared with 70 keV. Conclusions: Low-keV (40–50 keV) VMI on PCD-CT enhances bronchial artery visualization.